2021
DOI: 10.3390/molecules26237113
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Volatile Fingerprints of Four Chrysanthemum Teas Determined by HS-GC-IMS

Abstract: Volatile composition is an important feature that determines flavor, which actively affects the overall evaluation of chrysanthemum tea. In this study, HS-GC-IMS (headspace-gas chromatography-ion mobility spectrometry) was performed to characterize the volatile profiles of different chrysanthemum tea subtypes. Forty-seven volatiles of diverse chemical nature were identified and quantified. Partial least squares discriminant analysis (PLS-DA) revealed that four chrysanthemum teas were distinct from each other b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Volatile oils were one of the most important bioactive components in Chrysanthemum species, which are mainly composed of hydrocarbons, terpenoids, alcohols, esters, ketones, aldehydes, among others ( Ryu et al, 2019 ; Wang et al, 2021a ). The herbivory-induced emission of volatile terpenes in Chrysanthemum is an indirect defense against pest by attracting natural enemies ( Xu et al, 2021 ).…”
Section: Phytometabolites and Chemodiversity Of Chrysanthemummentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile oils were one of the most important bioactive components in Chrysanthemum species, which are mainly composed of hydrocarbons, terpenoids, alcohols, esters, ketones, aldehydes, among others ( Ryu et al, 2019 ; Wang et al, 2021a ). The herbivory-induced emission of volatile terpenes in Chrysanthemum is an indirect defense against pest by attracting natural enemies ( Xu et al, 2021 ).…”
Section: Phytometabolites and Chemodiversity Of Chrysanthemummentioning
confidence: 99%
“…Based on the volatile chemical profile of flower tea, Hangju, Huangju, chamomile ( Matricaria chamomilla ), and a new CM “Xiaokuixiang” were well distinguished from each other ( Wang et al, 2021a ). The main volatile components in chamomile were the ester ethyl 2-methylbutanoate and alcohol 1,8-cineole monomer, but the content of ketones in chamomile was relatively low; ethyl 2-methylbutanoate and ketone 6-methyl-5-hepten-2-one were more abundant in “Xiaokuixiang.” The terpenoids 6-methyl-5-hepten-2-one and 1-menthol monomer were salient in Hangju and Huangju, but very few esters were detected in both, agreeing with their close phylogenetic relationship.…”
Section: Phytometabolites and Chemodiversity Of Chrysanthemummentioning
confidence: 99%
“…The formation of different odorants does not necessarily result from a high number of volatile compounds [ 40 ]. Nevertheless, our study revealed that the relative content and quantity of volatile compounds of VCO in different locations have their own characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…HS-GC-IMS is a new technique developed in recent years for the detection of aromatic compounds, by which substances can be separated in two dimensions by GC and IMS drift tubes [ 30 , 31 , 32 , 33 , 34 ]. The method does not require complex sample pretreatment, and the sample can be directly injected after crushing, which has the advantages of environmental friendliness, high sensitivity and short analysis time [ 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%